Assessment of Aversion of Acute Pain Stimulus through Conditioned Place Aversion - Urien, Louise (Bio Protoc, 2017)
Pain is a complex experience. The aversive component of pain has been assessed through conditioned place aversion in rodents. However, this behavioral test does not allow the evaluation of the aversion of an acute pain stimulus. In Zhang et al. (2017), we provide an updated version of a Conditioned Place Aversion paradigm to address this challenge. In this protocol, a detailed version of this method is described.